2013
DOI: 10.1371/journal.pone.0076051
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in miRNA Levels in the Dentate Gyrus in Epileptic Rats

Abstract: The aim of this study was to characterize changes in miRNA expression in the epileptic dentate gyrus. Status epilepticus evoked by amygdala stimulation was used to induce epilepsy in rats. The dentate gyri were isolated at 7 d, 14 d, 30 d and 90 d after stimulation (n=5). Sham-operated time-matched controls were prepared for each time point (n=5). The miRNA expression was evaluated using Exiqon microarrays. Additionally, mRNA from the same animals was profiled using Affymetrix microarrays. We detected miRNA ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
4
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(118 citation statements)
references
References 58 publications
12
97
4
5
Order By: Relevance
“…miR-132, a miRNA that influences neuronal morphology by increasing dendritic outgrowth and arborization, and participating in regulation of spine density, is enriched in neurons and consistently up-regulated following epileptogenic stimuli (Jovičić et al 2013). Recently, Bot et al (2013) made an attempt to predict the functional impact of changes in miRNA expression during epileptogenesis by analyzing the expression of their potential mRNA targets. The data revealed that the protein products of miRNA-regulated mRNAs were involved in different types of molecular processes, including the regulation of transcription, second messenger signaling, ion homeostasis, immune response, response to wounding, and regulation of cell death (Bot et al 2013).…”
Section: Epileptogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…miR-132, a miRNA that influences neuronal morphology by increasing dendritic outgrowth and arborization, and participating in regulation of spine density, is enriched in neurons and consistently up-regulated following epileptogenic stimuli (Jovičić et al 2013). Recently, Bot et al (2013) made an attempt to predict the functional impact of changes in miRNA expression during epileptogenesis by analyzing the expression of their potential mRNA targets. The data revealed that the protein products of miRNA-regulated mRNAs were involved in different types of molecular processes, including the regulation of transcription, second messenger signaling, ion homeostasis, immune response, response to wounding, and regulation of cell death (Bot et al 2013).…”
Section: Epileptogenesismentioning
confidence: 99%
“…Recently, Bot et al (2013) made an attempt to predict the functional impact of changes in miRNA expression during epileptogenesis by analyzing the expression of their potential mRNA targets. The data revealed that the protein products of miRNA-regulated mRNAs were involved in different types of molecular processes, including the regulation of transcription, second messenger signaling, ion homeostasis, immune response, response to wounding, and regulation of cell death (Bot et al 2013). The significance of these complex changes in the expression of miRNAs during epileptogenesis is still difficult to interpret, and will require gathering more information on the function miRNA expression in the brain tissue and in-depth knowledge on the targets of each miRNA.…”
Section: Epileptogenesismentioning
confidence: 99%
“…This includes up-regulation of miR-146a and miR-132, as well as miR-9 and miR-99a [18], miR-27a and miR-203 [19] and miR-135a [21]. From those down-regulated, experimental models also detected miR-30a/b, miR-138, miR-324 and miR-330 [20] and miR-187 [21]. Nevertheless, this represents only ∼20% of the total regulated in human epilepsy.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, up- and down-regulated miRNAs may target the same genes in epilepsy [21]; without protein data the outcome is not possible to predict. The recent study by Bot et al offered an improved approach, combining mRNA data with miRNA to support functional targeting [20]. Ago2 pull-down studies can provide critical direct evidence that a miRNA is “functional”.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers suppose that such heterogeneity may be the result of the influence exerted by epilepsyinduced brain tissue damage to miRNA detection, thus choosing to conduct miRNA profiling in brain tissues extracted at least 2 months (chronic stage) after epileptic seizures. Four animal-based studies utilizing gene chips to identify miRNA expression, respectively conducted by Song et al [26] Hu et al [27] Bot et al [28] and Gorter et al [29], together reported about 25 differentially expressed miRNAs. Those mentioned in more than one of the studies include 14 up-regulated miRNAs and 9 down-regulated miRNAs.…”
Section: Micrornas Profiling In Different Time Phases After Sementioning
confidence: 99%